Evaluating the learning environment of nursing students: A multisite cross-sectional study. (August 2019) - Ramsbotham, Joanne; Dinh, Ha; Truong, Hue; Huong, Nguyen; Dang, Thanh; Nguyen, Chinh; Tran, Duong; Bonner, Ann
Abstract: Background: Identifying students' experiences of the university and clinical learning environments informs quality improvement of courses. Objectives: To investigate undergraduate nursing students' perceptions of their education environment and the facilitators and barriers to learning, during university and clinical experiences. Design: Multi-site cross-sectional survey. Setting: Four universities in Vietnam. Participants: Undergraduate nursing students ( n = 891). Methods: Between May and August 2016, Vietnamese versions of the Dundee Ready Education Environment Measure (Nursing) and the modified Clinical Learning Environment Inventory measured students' perceptions of university and clinical environments respectively. Two additional open-ended questions elicited perceptions of facilitators and/or barriers to clinical learning. Results: The university environment was rated as needing improvement and significant differences between universities and year of study detected. University environment mean scores were significantly higher in second year students compared with those in the third or fourth years of study. Active teaching and interpersonal relationships at university were rated positively. Overall, clinical environment scores were mid-range and second year students' mean scores were significantly higher than third or fourth years. Clinical placements greater than four weeks duration had significantly higher mean score than two week placements. Conclusions: Evaluation of university and clinical experiences assists with identifying potential areas of interruption to nursing students' transfer of learning. In both learning environments, Vietnamese students' experiences were similar to those experienced in Western countries in that interpersonal relationships with teachers and ward staff were key factors perceived to influence learning. A notable difference in this study was the hospital environment in Vietnam had features unique to this country that interrupted students' transfer of learning. Globally it is a priority for nurse educators to facilitate both on and off campus environments that promote students' learning. Assessing these environments is a useful strategy for quality improvement of courses. Highlights: Evaluating both on and off campus learning environments reveals conditions influencing students' transfer of learning. Students' experiences of interpersonal relationships with teachers and ward staff are key factors perceived to influence learning. The end users' experience of curricula informs course quality improvement.